Redoxal, an Inhibitor of De Novo Pyrimidine Biosynthesis, Augments APOBEC3G Antiviral Activity Against Human Immunodeficiency Virus Type 1 - Pery, Erez (Virology, 2015)
APOBEC3G (A3G) is a cytidine deaminase that restricts HIV-1 replication by inducing G-to-A hypermutation in viral DNA; deamination-independent mechanisms are also implicated. HIV-1 Vif protein counteracts A3G by inducing its proteasomal degradation. Thus, the Vif-A3G axis is a potential therapeutic target. To identify compounds that inhibit Vif:A3G interaction, a 307,520 compound library was tested in a TR-FRET screen.. Two identified compounds, redoxal and lomofungin, inhibited HIV-1 replication in peripheral blood mononuclear cells. Lomofungin activity was linked to A3G, but not pursued further due to cytotoxicity. Redoxal displayed A3G-dependent restriction, inhibiting viral replication by stabilizing A3G protein levels and increasing A3G in virions. A3G-independent activity was also detected. Treatment with uridine or orotate, intermediates of pyrimidine synthesis, diminished redoxal-induced stabilization of A3G and antiviral activity. These results identify redoxal as an inhibitor of HIV-1 replication and suggest its ability to inhibit pyrimidine biosynthesis suppresses viral replication by augmenting A3G antiviral activity.